The Relations of Attention to and Clarity of Feelings With Facial Affect Perception - Suslow, Thomas; Kersting, Anette (Frontiers in Psychology, 2022)
Attention to emotions and emotional clarity are core dimensions of individual differences in emotion awareness. Findings from prior research based on self-report indicate that attention to and recognition of one’s own emotions are related to attention to and recognition of other people’s emotions. In the present experimental study, we examined the relations of attention to and clarity of emotions with the efficiency of facial affect perception. Moreover, it was explored whether attention to and clarity of emotions are linked to negative interpretations of facial expressions. A perception of facial expressions (PFE) task based on schematic faces with neutral, ambiguous, or unambiguous emotional expressions and a gender decision task were administered to healthy individuals along with measures of emotion awareness, state and trait anxiety, depression, and verbal intelligence. Participants had to decide how much the faces express six basic affects. Evaluative ratings and decision latencies were analyzed. Attention to feelings was negatively correlated with evaluative decision latency whereas clarity of feelings was not related to decision latency in the PFE task. Attention to feelings was positively correlated with the perception of negative affects in ambiguous faces. Attention to feelings and emotional clarity were not related to gender decision latency. According to our results, dispositional attention to feelings goes along with an enhanced efficiency of facial affect perception. Habitually paying attention to one’s own emotions may facilitate processing of external emotional information. Preliminary evidence was obtained suggesting a relationship of dispositional attention to feelings with negative interpretations of facial expressions.